Exogenous Melatonin Directly and Indirectly Influences Sheep Oocytes - Chen, Yang; Shan, Xuesong; Jiang, Huaizhi; Guo, Zhenhua (Frontiers in Veterinary Science, 2022)
Understanding whether and how melatonin (MT) may impact sheep oocyte development competence is central to our ability to predict how sheep oocytes will respond to artificially regulated estrus. Implanting MT can make sheep enter estrus during the non-breeding season. One study found that the blastocyst rate increased under MT treatment, while another found that the blastocyst rate decreased. Therefore, we conducted a meta-analysis of MT directly and indirectly influencing sheep oocytes. A total of 433 articles were collected from which 20 articles and 34 treatments were finally selected. A method for estimating the default value was established for the litter size analysis. We found that exogenous MT add into in vitro maturation medium was positively related to the blastocyst rate in the lab. However, subcutaneous implanting MT did not affect the in vivo ovulation rate, fertilization rate, blastocyst rate, or pregnancy rate at farm. MT did not affect the in vitro cleavage rate. However, MT improved the in vivo cleavage rate. We hypothesized that implanted MT could increase the concentration of MT in oviduct fluid in vivo, and also that in vitro MT could increase the early cleavage rate of sheep zygotes without affecting the total cleavage rate. In the analysis of oocyte apoptosis caused by injury, the results suggested that pyroptosis would be more suitable for further research. MT produces responses in all body organs, and thus implanting of MT during non-breeding seasons should consider the effect on animal welfare.